Analisis Faktor Yang Memengaruhi Kejadian Hipertensi Pada Lansia Di Puskesmas Rasau Kab. Labuhanbatu Selatan - Febri Gustianda Ginanti Siregar; Deli Theo; Ramadhani Syafitri; Arifah Devi Fitriani; Yuniati Yuniati (Pusat Riset dan Inovasi Nasional, 2024)
According to the American Heart Association or AHA, Hypertension is a Silent Killer, with symptoms that can vary for each individual and are almost the same as the symptoms of other diseases. Blood pressure tends to increase with age i.e. people over 60 years old and this increase in blood pressure occurs naturally. Hypertension is a risk factor for various cardiovascular diseases and stroke. According to the AHA, hypertension is a disease that occurs due to an increase in systolic blood pressure > 140 mmHg or diastolic blood pressure > 90 mmHg.the purpose to be achived in this study is to determine and analyze the factors that influences the incident of hypertension in the elderly in puskesmas rasau south labuhanbatu district. This type of research uses a descriptive analytical survey with a cross sectional design. The population in this study were all elderly (≥60 years) sufferers of hypertension at the Rasau District Health Center. South Labuhanbatu as many as 148 people, while the sample was 108 people using slovin technique. The sampling technique was carried out using purposive sampling Data analysis was carried out using univariate, bivariate and multivariate analysis. Based on the results of the chi-square test, it is known that the incidence of hypertension has an influence of family history, smoking, obesity, diet and lack of physical activity on the incidence of hypertension p <0.05, meaning that there is an influence of family history, smoking, obesity, diet and lack of physical activity on the incidence of hypertension. . From the results of the multivariate analysis, it is known that the most influential variable in this study is the smoking variable with an OR value of 62,850. This means that respondents who smoke have a 62 times chance of influencing the incidence of hypertension at the Rasau District Health Center. South Labuhanbatu 2023. The conclusion in this study is that smoking is the most dominant factor influencing the incidence of hypertension at the Rasau District Health Center. South Labuhan Batu. In order to reduce the prevalence of hypertension, it is hoped that patients at the Rasau District Health Center. South Labuhanbatu must implement hypertension management with a healthy lifestyle, especially not smoking, so that hypertension sufferers can have controlled blood pressure levels.